PENGEMBANGAN PEMBELAJARAN INQUIRY BERVISI SETS PADA SISTEM PENCERNAAN UNTUK MENINGKATKAN KECERDASAN EMOSIONAL DAN PRESTASI BELAJAR - Trimo Susilo (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
ABSTRACTAttention to the issue of education is still lacking emotional intelligencedevelopment, but success is not determined by intelligence (IQ) alone, but rather by theemotional intelligence (EQ). Science learning process using appropriate methods andapproaches can improve emotional intelligence. Therefore the development of researchinquiry learning SETS vision on the concept of the digestive tract. The purpose ofresearch for new product development, testing the validity and effectiveness of theproduct in improving EQ and student achievement. Research methods research anddevelopment (R and D). Limited scale test was conducted in a classroom, using onesingle shot design case study. Large scale test was conducted in a control class, and twoexperimental class, using pretest-posttest designs control group. Research subjects inclass XI Science SMAN 3 Pekalongan. Test results show a valid product (criterion>0.81), the percentage achieving grades EQ experimental class > class control. T testresults showed t = 42.681 > t table = 2.025. Achievement of learning experimental class> class control. Conclusions of research, product development of valid and effective forimproving EQ and student achievement. Products recommended to be a reference devicedevelopment and learning to improve student achievement EQ.Keywords: Learning Inquiry, SETS, Emotional Intelligence